2014
DOI: 10.1037/neu0000087
|View full text |Cite
|
Sign up to set email alerts
|

Remote thalamic microstructural abnormalities related to cognitive function in ischemic stroke patients.

Abstract: Our findings support the hypothesis that ischemic stroke lesions are associated with remote thalamic diffusion abnormalities, and that these abnormalities can contribute to cognitive dysfunction 3 months after a cerebrovascular event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 82 publications
(118 reference statements)
1
23
1
Order By: Relevance
“…Santos and colleagues also demonstrate that secondary degeneration of thalamic nuclei via diaschisis can be associated with verticality misperception after stroke (44). In another study that evaluates patients at 3 months after stroke, the thalamic microstructural abnormalities detected by DTI imaging correlate with lower verbal fluency performance, suggesting the secondary abnormalities in thalamus are related to cognitive dysfunction (45). A prospective cohort study by Kuchcinski and colleagues demonstrate that the secondary thalamic alteration after focal cortical injury independently contributes to poor functional, cognitive and emotional outcome (46).…”
Section: Secondary Thalamic Injury Is Associated With Functional Behamentioning
confidence: 97%
“…Santos and colleagues also demonstrate that secondary degeneration of thalamic nuclei via diaschisis can be associated with verticality misperception after stroke (44). In another study that evaluates patients at 3 months after stroke, the thalamic microstructural abnormalities detected by DTI imaging correlate with lower verbal fluency performance, suggesting the secondary abnormalities in thalamus are related to cognitive dysfunction (45). A prospective cohort study by Kuchcinski and colleagues demonstrate that the secondary thalamic alteration after focal cortical injury independently contributes to poor functional, cognitive and emotional outcome (46).…”
Section: Secondary Thalamic Injury Is Associated With Functional Behamentioning
confidence: 97%
“…This phenomenon is characterized by a gradual and progressive neuroinflammatory response, which is inexorably coupled with cell death (Dihné et al, 2002;Iizuka et al, 1990;Pappata et al, 2000). With few exceptions, secondary neurodegeneration is associated with impaired functional recovery (Binkofski et al, 1996;Fernández-Andújar et al, 2014;Seitz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have identified that the thalamus is particularly sensitive to neurodegeneration post-stroke, with thalamic disturbances emerging within weeks of infarction and persisting in some cases for up to two years (Fernández-Andújar et al, 2014;Gerhard et al, 2005;Herve et al, 2005;Kataoka et al, 1989). Neuroimaging studies have revealed that there is a significant increase in mean http://dx.doi.org/10.1016/j.bbi.2015.02.014 0889-1591/Ó 2015 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SND involves the progressive death of neurons that were connected to the site of infarction but not initially damaged by the stroke. SND unfolds over a longer time scale than the infarction process and has recently been implicated as a potential modulator to a number of late phase functional recovery disturbances (Chen, Garcia, Huang, & Constantini, ; Dang et al, ; Fernandez‐Andujar et al, ).…”
Section: Introductionmentioning
confidence: 99%